Teachers Assessment of Needs Satisfiers as Motivation for Effectiveness in Rivers State Primary Schools in Nigeria - Ikenyiri, Emmanuel; Maduenyi, Richard Ihua (Mediterranean Journal of Social Sciences, 2012)
This study examined teachers assessment of needs satisfies as motivation for teachers’ effectiveness in Rivers Stateprimary schools. To collect data for the study, a questionnaire Titled, Teachers Assessment of Needs Satisfiers that MotivateTeachers Effectiveness, (TANSMTEQ) was used. The questionnaire had 20 items drawn from Abraham Moslow’s Hierarchy ofneeds categorized into five. The items were also drawn to answer the 5 research questions of the study. The findings show thatthe teachers assessed physiological needs such as prompt payment of salary for provision of food and clothing, enhanced: rent,transport and medical allowances. For the security needs, teachers assessed need for protection against dismissal, need forprotection against threat from pupils and parents. There were also assessment of social needs, self-eastern needs and selfactualizationneeds. Conclusion and recommendations such as government should provide basic needs that will make teachershappy and effective in their job.